Childhood psoriasis and serum calcium levels. - Maheswari, A.; Dutta, B. (European Journal of Pediatric Dermatology, 2020)
Childhood psoriasis is a common dermatological disorder with massive psychological impact. The objective was to study the clinical profile of children with psoriasis and analyze the serum calcium levels and to find any correlation of calcium levels with severity or type of psoriasis. The study consisted of 56 children with childhood psoriasis, carried out over a period of 1 year. Detailed clinical data were noted and serum calcium levels were evaluated. Prevalence was found to be 0.75%, with females outnumbering males. Hypocalcemia was found in 5 (8.9%) patients, with significant association found with pustular psoriasis, indicating the role of correcting calcium levels to prevent development of severe forms of psoriasis. A moderately strong negative correlation was found between severity of psoriasis vulgaris and serum calcium levels. Hence, dietary supplements can play a major role in preventing progression to severe forms of the disease and provide a better outcome.